2013
DOI: 10.1093/humrep/det238
|View full text |Cite
|
Sign up to set email alerts
|

Profibrotic interleukin-33 is correlated with uterine leiomyoma tumour burden

Abstract: No funding, no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…Chronic inflammation is associated with an overproduction of prostaglandins [17], metalloproteinases, cytokines and chemokines, creating a self-supporting loop that mantains and amplificates the progression of the disease [1820]. Once the process is started, many profibrotic mediators also play a role in the fibrogenesis associated with endometriosis [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Chronic inflammation is associated with an overproduction of prostaglandins [17], metalloproteinases, cytokines and chemokines, creating a self-supporting loop that mantains and amplificates the progression of the disease [1820]. Once the process is started, many profibrotic mediators also play a role in the fibrogenesis associated with endometriosis [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Among major cytokines, the expression of IL-1, IL-6, IL-11, IL-13, IL-15, IL-33, tumor necrosis factor (TNF) a, granulocyte-macrophage colony-stimulating factor have been implicated with their biological relevance to leiomyoma pathophysiology. 18,[40][41][42] Additionally, TGF-b has been shown to be overexpressed in leiomyomas versus myometrium and be both mitogenic and fibrogenic in these tissues. 43 Additional researches have demonstrated that TGF-b, IL-1 and TNF influence the secretion of enzymes (MMP2 and MMP9), 44 and IL-6 may induce hepatic C-reactive protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of inflammation actually fits into a theory of fibroid development based on an altered response to noxious stimuli; possibly tissue injury from extravasated menstrual blood into the myometrium, or hypoxia leading to altered tissue repair and fibrosis . Among major cytokines, the expression of IL‐1, IL‐6, IL‐11, IL‐13, IL‐15, IL‐33, tumor necrosis factor (TNF)‐α, granulocyte‐macrophage colony‐stimulating factor have been implicated with their biological relevance to leiomyoma pathophysiology . The expression profiles of many chemokines and chemokine receptors have also been characterized in leiomyomas and matched myometrium.…”
Section: Pathogenesis Of Uterine Fibroidsmentioning
confidence: 99%
“…been implicated with their biological relevance to leiomyoma pathophysiology [42][43][44][45][46][47]. The expression profiles of many chemokines and chemokine receptors have also been characterized in leiomyomas and matched myometrium.…”
Section: Resveratrolmentioning
confidence: 99%